Festivals and Urban Space: Sociology of Three Urban Festivals in Klaipeda - Kraniauskas, Liutauras (Sociologija. Mintis ir veiksmas, 2011)
The article explores complex relationship between festivals, urban spaces and consumption. The study of three city festivals - Sea Festival, Jazz Festival and short films festival ‘Tinklai’ - in Klaipeda, Lithuania, over the period 1991-2010 reveals that changes of festivals’ locations in the city were mainly stimulated by consumption. The festivals gradually move to those urban spaces, which lost their functionality and are easily converted into the temporary places of controlled consumption. Despite the fact that usually festivals set urban spaces for new sociality of emotional community, physical arrangements of festival territories reproduce more general patterns of social distinctions and hierarchies. Urban festivals convert postindustrial territories into places of consumption and shape discourse of consuming city. Methodological assumptions of the study are based on P. Bourdieu’s typology of taste, M. de Certeau’s idea of urban space signification practices, and H. Lefebvre’s theory of urban space production.